2012
DOI: 10.5539/jms.v2n1p29
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Management Applications in Rejuvenation Efforts of South-Western Nigerian Hotels: Facilities Management Perspective

Abstract: A survey was conducted of probabilistically determined fifty-seven hotels of various 'stars' in South-Western geo-political zone of Nigeria to investigate the responsiveness of the hotel organizations to strategic property management practices in particular level of use of facilities management, level of commitment to business development, use of information and communication technology and support services procurement methodology. Data were collected from hotel organizations through their general managers, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…The mean ranking analysis results of ten (10) key services provided by hotels which indicated the most common service provided by the sampled hotels in the study area is accommodation with mean of 4.8790 while the least electricity warmed swimming pools with mean of 2.2102 was not surprising because accommodation provision is the primary objective of hotel facilities. The outcome is also consistent with the study findings of Durodola (2009) and Järvensivu (2014) which indicated that accommodation provision is the core product of hotel organizations to which other facilities are adjunct to or are augmented products. Their argument is further substantiated by Bevan (1991) which suggested that hotel facilities are instruments of marketing accommodation.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The mean ranking analysis results of ten (10) key services provided by hotels which indicated the most common service provided by the sampled hotels in the study area is accommodation with mean of 4.8790 while the least electricity warmed swimming pools with mean of 2.2102 was not surprising because accommodation provision is the primary objective of hotel facilities. The outcome is also consistent with the study findings of Durodola (2009) and Järvensivu (2014) which indicated that accommodation provision is the core product of hotel organizations to which other facilities are adjunct to or are augmented products. Their argument is further substantiated by Bevan (1991) which suggested that hotel facilities are instruments of marketing accommodation.…”
Section: Resultssupporting
confidence: 89%
“…Other identified key services provided after accommodation include restaurant with mean of 4.6879, internet with mean value of 4.3439, and laundry with mean value of 4.2420 and the least provided services after electricity warmed pools by the hotels in the study area were outdoor catering with mean value of 3.3567 and shopping centres 3.3885 these results were in line with study findings of Durodola (2009) where the findings revealed glaring deficiency in areas of recreation (24%), and shopping facilities (29%) provision in the hotels studied in South-west Nigeria. The findings from mean ranking of five (5) basic energy resources utilized indicates electricity (Grid supplied), diesel and gas respectively are the major energy sources used in the study area.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…While facilities management incorporates maintenance management as well as property management no element of facilities management or property management can be found in the coverage of maintenance management. Whereas, maintenance activity is an element of property and facilities management but facilities management is not an element of maintenance management or of property management (Durodola, 2009). Thus, facilities management could be regarded as a strategic management tool that readily comes in when there is a need to re-invigorate the performance of property investment (Telfer, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%